SEMANTICS AND STYLISTICS OF PHRASEOLOGICAL UNITS IN ARABIC LANGUAGE (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the semantic and stylistic characteristics of Arabic phraseological units with particular emphasis on zoonymic phraseology. Phraseological units are regarded as an essential component of linguistic and cultural heritage, reflecting the worldview, traditions, customs, and historical experience of Arabic-speaking communities. The study analyzes the semantic transformation and figurative meanings of phraseological expressions derived from animal names and demonstrates their stylistic functions in literary and everyday discourse. Special attention is devoted to the symbolic meanings of zoonyms in Arabic culture, their occurrence in classical Arabic literature, the Holy Qur’an, and traditional proverbs. The paper also investigates comparative phraseological constructions and explores the similarities and differences between Arabic and Uzbek zoonymic expressions. The findings reveal that Arabic phraseological units preserve national-cultural values while simultaneously demonstrating universal cognitive mechanisms shared across languages through metaphorical conceptualization and symbolic representation.
Keywords: Arabic phraseology, semantics, stylistics, zoonymic phraseological units, metaphor, semantic transformation, comparative phraseology, Arabic culture, symbolism, linguistic worldview.